HUKUM IJTIHAD DALAM PROSES LEGISLASI HUKUM ISLAM - Khoirul Hadi (Faculty of Sharia and Law UNISNU Jepara, 2014)
This study is based on library research and departs from the understanding of the ijtihad meaning, and importance of reviewing whether the legal process of ijtihad has a strong legal basis, or only reasonable attempts to trick the text, or ijtihad is mandatory. Since if there is no ijtihad then the text is only inanimate object that can not be useful to himself or otherwise. This study uses the science of ushul fiqh to dissect whether it is true that, methodologically, ijtihad is required. Based on this research it is known that ijtihad is absolutely required in Islamic law. But, that is only for those who are really capable and mastering all requirements needed. Instinbath al-hukm in modern era must be executed continously and simultaneously so it can result very sulotive and useful legal products for society in general.Keywordsijtihad, obligatory, ushul fiqh, Islamic law Penelitian berbasis library research ini berangkat dari pemahaman pentingnya memaknai dan mengkaji ulang apakah secara hukum proses ijtihad mempunyai sandaran hukum yang kuat, ataukah hanya upaya akal untuk mengelabui teks, ataukah memang ijtihad itu wajib, karena jika tidak ada ijtihad maka teks adalah hanya benda mati yang tidak bisa berguna bagi dirinya sendiri atau sebaliknya. Kajian ini menggunakan ilmu ushul fikh untuk membedah apakah benar secara metodologi ijtihad itu diperlukan. Dari penelitian ini diketahui bahwa dalam hukum Islam ijtihad sangat diharuskan, akan tetapi bagi kalangan yang benar-benar mampu dan menguasai ijtihad dengan segala persyaratannya. Istibath al-hukm dalam era modern ini harus dilakukan dengan kontiunitas dan berkesinambungan, sehingga dihasilkan produk hukum yang mumpuni dan berguna bagi masyarakat secara umum.